Use Of Firearms By Police Forces In The Perspective Of Legal Sociology: A Study On Violence Control And Human Rights - Padhilah, Piqi Rizki; Rojikin, Umar; Saebani, Beni Ahmad (PALAR (Pakuan Law review), 2025)
AbstractThe use of firearms by police officers is a complex issue that intersects the necessity of maintaining public security with the obligation to uphold human rights. This study explores the legal and sociological perspectives on the use of force, particularly firearms, by law enforcement officers in controlling violence and addressing human rights concerns. The analysis employs a literature review method, examining various legal frameworks, academic studies, and case studies. The findings reveal that while regulations such as Chief of Police Regulation No. 1 of 2009 provide a legal foundation, implementation in the field often deviates from the principles of proportionality and human rights respect. This highlights the need for comprehensive reforms in policy, monitoring, and training to ensure that law enforcement actions align with justice and human rights standards. This study underscores the importance of integrating sociological insights into the legal framework to achieve balanced law enforcement practices. Keywords : Firearms; Sociology of law; Human rights; Violence control; Police regulation.